2003
DOI: 10.1093/nar/gkg696
|View full text |Cite
|
Sign up to set email alerts
|

Clerocidin alkylates DNA through its epoxide function: evidence for a fine tuned mechanism of action

Abstract: Clerocidin (CL) is an effective topoisomerase II-poison, which has been shown to produce DNA depurination and strand breaks per se at the guanine (G) level. To elucidate the roles played by the different functional groups of CL in the reactivity towards nucleic acids, we investigated CL derivatives with key structural modi®cations. The derivatives were reacted with plasmid, single-/double-stranded DNA and isolated 2¢-deoxy-guanosines (dG). We show here that an intact oxirane ring is essential to achieve DNA mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…The C12–C15 moiety of the drug is responsible for the cleavage activity; in particular, spontaneous DNA fragmentation derives from depurination at the G level caused by the electrophilic attack of the epoxide ring of CL on the N7 group of exposed Gs ( 6 ). The hemi-acetalic form of the α-ketoaldehyde function at C14–C15 enhances epoxide reactivity by applying additional strain to the oxirane ring ( 7 ). On the other hand, the diterpenoid portion of CL is dispensable for drug activity per se ; in fact the NA1 analogue of CL ( Figure 1 ), which preserves the C12–C15 ring but has the diterpenoid function substituted with naphthalene retains intrinsic DNA cleavage activity ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The C12–C15 moiety of the drug is responsible for the cleavage activity; in particular, spontaneous DNA fragmentation derives from depurination at the G level caused by the electrophilic attack of the epoxide ring of CL on the N7 group of exposed Gs ( 6 ). The hemi-acetalic form of the α-ketoaldehyde function at C14–C15 enhances epoxide reactivity by applying additional strain to the oxirane ring ( 7 ). On the other hand, the diterpenoid portion of CL is dispensable for drug activity per se ; in fact the NA1 analogue of CL ( Figure 1 ), which preserves the C12–C15 ring but has the diterpenoid function substituted with naphthalene retains intrinsic DNA cleavage activity ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The natural compound CL had been previously shown to be able to detect and induce cleavage in partially ss regions within supercoiled plasmids, whereas it resulted completely inert versus ds nucleic acids [17], [18]. Here we showed that CL could detect the presence of non-paired sequences, when at least one ss non-T base was available, in a number of non-canonical DNA conformations.…”
Section: Discussionmentioning
confidence: 63%
“…However, total synthesis of CL has been reported [38] and a structural analogue, in which the diterpenoid moiety is replaced by a naphthalene ring while preserving base selectivity and reactivity, can be easily synthesized [18], [19], [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the initial adduct formation other processes may occur. For example, alkylation of the N7‐position in 2′‐deoxyguanosine often leads to deglycosylation11 and sometimes to imidazole ring opening 9. In order to identify all these different theoretically possible structures a classical LC/MS/MS approach is quite time‐ and sample‐consuming.…”
mentioning
confidence: 99%